The effect of vlog media on speaking skills for the elt students during the outbreak covid 19 pandemics - Arri Kurniawan; Tri Wulandari; Angela Valentiara Giofanny (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
This study aims to investigate the effect of vlog media on speaking skills for the elt students during the outbreak covid 19 pandemics. This is a quasi-experimental study. This research took place at Department of English Education, Universitas PGRI Madiun. The sample of this research is the second semester students. Random sampling was used in this study. There were 64 students involved in this study: 32 of them belonged to the experimental group and the rest belonged to the control group. Test results from the experimental class and the control class' pre- and post-tests were used as the data to be interpreted. The researcher used statistical calculations from the independent t-test (SPSS) to analyze the data from the post-test. Based on the description of the result of the study, it can be stated that the use of vlog media in teaching speaking is very nice and interesting. It can encourage the students to perform their skill in using English language. Future researchers are encouraged to use vlog media with other design of the study.